If it's not what You are looking for type in the equation solver your own equation and let us solve it.
96=-6x-6(x-6)
We move all terms to the left:
96-(-6x-6(x-6))=0
We calculate terms in parentheses: -(-6x-6(x-6)), so:We get rid of parentheses
-6x-6(x-6)
We multiply parentheses
-6x-6x+36
We add all the numbers together, and all the variables
-12x+36
Back to the equation:
-(-12x+36)
12x-36+96=0
We add all the numbers together, and all the variables
12x+60=0
We move all terms containing x to the left, all other terms to the right
12x=-60
x=-60/12
x=-5
| -6(8x+2)=-5x-12 | | y+1/2=74/5 | | X3•2x2=8x | | 2x+5(2x-6)-8x=2x+6 | | 5(2x-1)=7x-5 | | 2x+62+54-x+5x-20=180 | | 5(4+2x)=8(X+9 | | x2–4x+4=36 | | x+6+3=10 | | 1/4=15x(+2) | | D=28t-56 | | 6x+5(4-2x)=4(3-x) | | 5x+11=3x-11 | | (x-24)+(5x)=180 | | 6x-3x+10=2x+6 | | 5−2g=1 | | 2x+62+54-x=5x-20=180 | | 8-5x=20+7x | | 8+z-10=0 | | 5/4z−5=10 | | 9⎛⎝r−r12⎞⎠=−3r12−5 | | 8x=-32-6x=48 | | x-24)+(5x)=180 | | 3(80-9x)=x=-96 | | (2/7)y=4 | | 8x=-326x=48 | | -340=-3x-5(7x+30) | | 3-5(2x+1)=10. | | x-24+(5x)=180 | | 2/7•y=4 | | 3(2t-3)=31-2(2t-5) | | 2(10-2y)+y=8 |